179k views
1 vote
Simplify the power (-3x^2y)^4

User AndiDog
by
5.1k points

2 Answers

5 votes

⇒In this case I will use the law of exponents that states:


(x^(m) )^(n) \\=x^(m*n)


=(-3x)^(2y*4) \\=(-3x)^(8y)

User Dreamwagon
by
5.4k points
5 votes

Answer: 81x^8y^4

Explanation:

1. DISTRIBUTE EXPONENT by using the power rule: (ab)^n = (a^n)(b^n)

> Apply PRODUCT RULE: -3x^2y = (-3x^2)^4y^4

>Apply PRODUCT RULE: -3x^2 = (-3)^4 (x^2)^4y^4

2. RAISE -3 to the power of 4 = 81(x^2)^4y^4

3. MULTIPLY THE EXPONENTS in (x^2)^4

> Apply POWER RULE and MULTIPLY EXPONENTS, (a^m)^n = a^mn

(81x^2*4)(y^4)

> MULTIPLY 2 by 4 = 81x^8y^4

And that is your answer, 81x^8y^4

User Ryan Rahlf
by
5.0k points